In the Face of Anti-LGBQ Behaviour: Saskatchewan High-school Students’ Perceptions of School Climate and Consequential Impact - Morrison, Melanie A; Jewell, Lisa M; McCutcheon, Jessica M; Cochrane, Donald B (Canadian Journal of Education/Revue canadienne de l’éducation, 2014)
In Canada, there is a dearth of research on school climate for lesbian, gay, bisexual, and questioning (LGBQ) students. Using social networking, sixty students from high-schools in Saskatchewan participated in a climate survey. Results indicated that anti-LGBQ speech is widespread, as were other forms of harassment. The more victimization that was reported by students known, or perceived to be, LGBQ, the more deleterious were the consequences for their academic performance, social lives, participation in sports and extra-curricular activities, and overall enjoyment of school. Limitations associated with the study and directions for future research are detailed.